PENERAPAN METODE MEMBACA GRAFIK PADA PEMBELAJARAN KIDUNG DI DALAM SEKAA SANTI SUNARI MAS - Nanda Jaya Pratama, I Gede (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2025)
Dharma gītā is part of the approach in the field of study of Pendidikan Agama Hindu dan Budi Pekerti, one of which is kidung. Besides being taught in formal education, dharma gītā is also taught in non-formal education. Non-formal learning of kidung in this study was carried out in Banjar Batu Mas, especially with Sekaa Santi Sunari Mas. This research uses descriptive qualitative methods by conducting several ways of collecting data, including observation, documentation, and interviews. The research was conducted for 12 weeks with two samples of material namely Kidung Kawitan Wargasari and Kidung Bramara Ngisep Sari which used visual media in the form of kidung charts. The results of this study are the form of planning the implementation of kidung learning using the graphic method which consists of five steps, namely: 1.) Organizing the study group; 2.) Analyzing the background and needs of the learning community; 3.) Designing and preparing kidung learning; 4.) Implementing learning; and 5.) Evaluation of learning implementation. From the two kidungs, researchers took three patterns each that represented all forms of kidung graphic patterns as a whole. The examples introduce rhythmic forms in line graph patterns, ceciren or markers that form ngumbang and ngisep patterns, and the tempo of the kidung tone.